UCLA' s Licenciatura en Desarrollo Humano: Balance of an experience (Mayéutica Revista Científica de Humanidades y Artes, 2023)
Speech delivered on March 9, 2017 at the Universidad Centroccidental Lisandro Alvarado (UCLA), on the occasion of the 10th Anniversary of the Licenciatura en Desarrollo Humano, by its founder and first director, Dr. Mauricio Iranzo Tacoronte, at the Ambrosio Oropeza Auditorium of this University.
Keywords: human development; Universidad Centroccidental Lisandro Alvarado; Licenciatura en Desarrollo Humano; complexity; uncertainty